Marketing Innovation as a Strategic Approach to Increasing Customer Preference in Pesantren-Based Education - Ella Shofiatun Azizah; Akmal Mundiri (Al-Qalam Institue, 2023)
The purpose of this study is to analyze the forms of educational marketing innovation implemented in Islamic Boarding Schools, to examine the challenges faced in their implementation, and to identify their impact on customer preferences. Pesantren are no longer viewed solely as traditional religious institutions but are also required to develop adaptive and innovative marketing strategies to remain relevant and competitive in the era of modernization and digital transformation. This study employed a qualitative approach using a multi-case study design. Data were collected through observation, in-depth interviews, and documentation at both pesantren. The data were analyzed thematically by comparing patterns of marketing innovation and customer preferences across the research sites. The findings reveal that both pesantren have implemented various marketing innovations, including the utilization of social media for promotion, strengthening institutional narratives and branding, adopting the Merdeka Curriculum-based educational system, and involving alumni as promotional agents. However, several challenges were identified, such as limited human resources, resistance to organizational change, and digital disparities among administrators. Despite these obstacles, the marketing innovations positively influenced customer preferences, as indicated by increased student enrollment and stronger public trust in the institutions.